2021
DOI: 10.1002/pc.26180
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on multiwalled carbon nanotube nanocomposite piezoresistivity considering the filler agglomeration effects

Abstract: Piezoresistive strain sensing of multiwalled carbon nanotube (CNT)reinforced polymer nanocomposites considering the effect of agglomeration is experimentally investigated. Thermoplastic polyurethane is used as composite matrix with melt mixing method for fabricating the nanocomposite. The electrical resistance of the nanocomposite specimens is measured by a designed electrical circuit in conductivity and piezoresistivity tests. The electrical resistance of the nanocomposite decreases by a nonlinear relation wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…This indicates a weakened interface between the rubber matrix and the fluorescent powders, resulting in defects within the sample. These defects may lead to a deterioration of the sample's mechanical properties, [42] consistent with the previously mentioned changes in its mechanical performance.…”
Section: Crosslinking Of Luminescent Elastomerssupporting
confidence: 77%
“…This indicates a weakened interface between the rubber matrix and the fluorescent powders, resulting in defects within the sample. These defects may lead to a deterioration of the sample's mechanical properties, [42] consistent with the previously mentioned changes in its mechanical performance.…”
Section: Crosslinking Of Luminescent Elastomerssupporting
confidence: 77%
“…Therefore, with the addition of more HGB, the ILSS value of the material begins to decline. When it increases to a certain extent, HGB contacts with each other, forming the agglomeration phenomenon, resulting in a large number of defects 45 . And in the molding process of composite sheets, the migration of HGB to the interlayer can no longer form an effective barrier to the expansion of microcracks, but severely damage the bonding ability between the layers of the material, so that the interlayer shear strength decreases rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2C already showed the presence of agglomerates in 1.2 wt% nanocomposites and the agglomeration could also decrease the strain sensitivity of nanocomposites which is also evident from the literature study. [ 43 ] Also, the increased viscosity and lack of free space available for fiber rotation result in improper alignment at higher CNF content. [ 8 ] A similar kind of observation on the effect of filler alignment on piezoresistive sensing of nanocomposites was also reported by Oliva‐Alives et al, where the alignment effect on sensing was found to be more evident at lower filler concentrations.…”
Section: Resultsmentioning
confidence: 99%